An in-depth inquiry into family planning values, beliefs and practices of Muslims in southern Philippines - Cabaraban, Magdalena C. (2006)
This formative research aimed to probe into the knowledge, attitudes, and beliefs regarding family planning and related issues of Muslim Filipinos in the Autonomous Region in Muslim Mindanao (ARMM). The study sites comprised six communities purposively chosen from each of the five provinces and onve city in ARMM. A total of 39 focus group discussions involving 278 participants and 159 in-depth interviews were conducted. The findings highlight the value of children, the practice of arranged marriages, and the problems of premarital and unintended pregnancies. The desired number of children varies: the young married respondents express preference for a smaller number; the low-educated and traditional ones want many children. A large number of respondents are aware of family planning methods. Their knowledge, however, is deficient and limited. There is widespread awareness of the traditional method. Misperceptions are plenty and fears are mostly on side effects. Methods currently used include both the modern and the traditional. Health providers at the local health centers and hospitals are considered the best sources of information regarding health and family planning. Radio and television, adjudged as influential and credible, are poorly considered because these channels are considered for entertainment only. Ethnicity does not serve as a guide in making important decisions. Decisions on whether or not to adopt family planning and decision on the number of children are guided by being a Muslim, not by ethnic affiliation. The study recommends the application of appropriate advocacy approaches, development of culture and gender-sensitive IEC materials, prioritization of special groups, and development intervention for the empowerment of women. Alternative channels of information dissemination or piloting of modalities in information-education need to be developed, pre-tested and evaluated in terms of their effectiveness to change behavior.